Human biology - Starr, Cecie (Thomson Brooks/Cole, 2005)
The chapter opening "Impacts, Issues" case study focuses students on a key biology-related societal issue and is revisited throughout the chapter. Then the chapter's "How Would You Vote?" feature asks students to consider a related news topics, gather and evaluate pro/con information, apply knowledge, and cast a vote on the Web